Propuesta de un plan de gestión integral de residuos sólidos domiciliarios generados en la cabecera cantonal de Catacocha, cantón Paltas, provincia de Loja - Tacuri Bacuilima, Anghelo Paolo (2018)
Abstract:In Ecuador, studies on the generation and composition of domestic solid waste have been carried out, but in small urban areas they have not been executed, such is the case of the cantonal head of the Catacocha canton of Paltas, which currently lacks a comprehensive waste management plan residential solids; for this reason the research of this project is undertaken, whose general objective was to design a plan for the integral management of solid household waste, applying a theoretical-practical methodology that allowed collecting information, evaluating the collection system and the current management of solid waste, and characterize the household solid waste generated. The results revealed that the GPC of average waste is estimated at 0.44kg /hab*day; the composition of solid waste is mostly organic waste, followed by inorganic waste, where plastic predominates; most of the population has a collection service; One weakness of the Department of Environmental Management is the low budget allocation assigned. Finally, a comprehensive waste management plan was designed covering 4 programs that were socialized with the main stakeholders involved.